Caso de estudio: accesibilidad de los microcréditos en el sector financiero popular y solidario, cantón El Guabo, 2021. - Ordoñez Pacheco, Angel Fernando; Aguilar Bazaran, Byron Joel (Machala : Universidad Técnica de Machala, 2023)
The Popular and Solidarity Financial Sector has been configured as one of the sectors that has provided the most financing to the vulnerable population and to the various productive activities in various provinces of the country through its credit instruments. The investigation lies precisely in determining the factors that affect the granting of microcredits of the entities of the Popular and Solidarity Financial Sector, through the use of binary and scale variables, in the businesses of the Popular and Solidarity Economy of the canton El Guabo, 2021, seeking the promotion of alternatives that produce an increase in financial resources available to merchants, taking this canton due to the scarcity of information that exists on this subject. For the realization of the study, a descriptive, non-experimental and correlational methodological line was followed, using the maximum likelihood method that revealed the importance of promoting financial education among merchants, through training on topics such as managing financial resources and preparation of a long-term sustainable budget, which will increase the chances of accessing a microcredit in entities in this sector by 9%.
El Sector Financiero Popular y Solidario se ha configurado como uno de los sectores que mayor financiamiento ha brindado a la población vulnerable y a las diversas actividades productivas en diversas provincias del país a través de sus instrumentos crediticios. La investigación yace en precisar los aspectos que influyen en la concesión de microcréditos de las organizaciones del Sector Financiero Popular y Solidario, a través del uso de variables binarias y de escala, en los comercios de la Economía Popular y Solidaria del cantón El Guabo, 2021, buscando la promoción de alternativas que produzcan un aumento de los recursos financieros a disposición de los comerciantes, tomando a este cantón por la escasez de información que existe de esta temática. Para la concreción del estudio, se siguió una línea metodológica de tipo descriptiva, no experimental y correlacional, empleando el método de máxima verosimilitud que reveló la importancia de promover la educación financiera entre los comerciantes, por medio de la capacitación en temas como el manejo de los recursos financieros y elaboración de un presupuesto sostenible a largo plazo, que aumentará en un 9% las posibilidades de acceder a un microcrédito en las entidades de este sector.
Keywords: SECTOR FINANCIERO POPULAR Y SOLIDARIO; MICROCREDITOS; COMERCIANTES